Midlife suicide: A systematic review and meta-analysis of socioeconomic, psychiatric and physical health risk factors. (October 2022) - Qin, Ping; Syeda, Sadia; Canetto, Silvia Sara; Arya, Vikas; Liu, Baopeng; Menon, Vikas; Lew, Bob; Platt, Stephen; Yip, Paul; Gunnell, David
Abstract: Suicide is an increasing contributing cause of mortality in middle-aged adults; however, knowledge to guide prevention is limited. This first systematic review and meta-analysis of studies on midlife suicide has provided an overview of published research on this issue and synthesized the evidence on socioeconomic and physical and mental health factors associated with this mortality. Using PRISMA guidelines MEDLINE, Embase, PsycINFO, Scopus and Web of Science were searched for English-language publications that involved persons aged 35 to 65, used individual-level data, and reported prevalence of exposure(s) or relative risks. The search identified 62 studies on midlife suicides and associated factors (28 for SES, 22 for psychiatric disorder and 23 for physical illness). All studies were from high income countries, and most (80.6%) used data from population registries. Meta-analyses showed that the pooled prevalence of exposure in suicide decedents was 57.8% for psychiatric disorder, 56.3% for low income, 43.2% for unemployment, and 27.3% for physical illness. The associated pooled risk ratio was 11.68 (95% confidence intervals: 5.82–23.47) for psychiatric illness of any type, 12.59 (8.29–19.12) for mood disorders, 3.91 (2.72–5.59) for unemployment, 3.18 (2.72–3.72) for being separated or divorced, 2.64 (2.26–3.10) for cancer, 2.50 (0.96–6.38) for central nervous system illness, and 2.26 (1.16–4.41) for low income. In conclusion, midlife suicide is strongly associated with socioeconomic difficulties and physical and psychiatric illnesses that are common in this age population. Future investigations should consider the interactions between risk factors, the intersectionality of sex and ethnicity, and include data from low- and middle-income countries.